ChemInform Abstract: Discovery of a New Palladacycle Precatalyst and Its Applications to C—O Coupling Reactions Between Electron‐Deficient Phenols and Functionalized Heteroaryl Chlorides. Issue 35 (September 2015) - Zhang, Ting; Tudge, Matthew T.
Abstract A novel Pd‐precatalyst is designed, synthesized, and successfully applied in the challenging synthesis of diaryl ethers (III) from functionalized electron‐deficient hetaryl chlorides (II) and electron‐deficient phenols (I).